Vitamin D: Are We Ready to Supplement for Breast Cancer Prevention and Treatment?. (26th February 2013) - Crew, Katherine D.
Abstract : Vitamin D deficiency is a potentially modifiable risk factor that may be targeted for breast cancer prevention and treatment. Preclinical studies support various antitumor effects of vitamin D in breast cancer. Numerous observational studies have reported an inverse association between vitamin D status, including circulating 25-hydroxyvitamin D (25(OH)D) levels, and breast cancer risk. The relationship between vitamin D and mammographic density, a strong predictor of breast cancer risk, remains unclear. Studies analyzing the link between genetic polymorphisms in vitamin D pathway genes and breast cancer incidence and prognosis have yielded inconsistent results. Vitamin D deficiency among breast cancer patients has been associated with poorer clinical outcomes and increased mortality. Despite a number of clinical trials of vitamin D supplementation, the efficacy, optimal dosage of vitamin D, and target blood level of 25(OH)D for breast cancer prevention have yet to be determined. Even with substantial literature on vitamin D and breast cancer, future studies need to focus on gaining a better understanding of the biologic effects of vitamin D in breast tissue. Despite compelling data from experimental and observational studies, there is still insufficient data from clinical trials to make recommendations for vitamin D supplementation for breast cancer prevention or treatment.